Teaching Sociolinguistics: A Medium for Cultural Awareness of Indonesian University Foreign Language Learners - Agnes Herawati (Humaniora, 2014)
This paper tries to show the evidences that indicate how teaching Sociolinguistics can result in a number of valuable outcomes, including helping students understand and appreciate other cultures different from theirs. Sociolinguistics provides useful examples of language usage in different genres, including how culture influences people in using a language. The opportunities of learning other cultures through language will take the students to the higher level of appreciation of the culture of the target language. To determine how this outcome can be achieved in the language classrooms, this paper provides a review of closely connected literature about how to bridge the gap between cultures in particular. However, to increase its completeness and relevance, this paper also provides some research results that reveal how teaching Sociolinguistics has taken its new applicability and importance, and furthermore adds the effects on how students become more proficient and enthusiastic about their learning.